Levonorgestrel intrauterine contraceptive device in heavy menstrual bleeding: our experience in a tertiary level government hospital - Malik, Renuka; Gupta, Jagrati; Singh, P.; Yadav, Poonam (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: The aim of the study was to assess the effect of levonorgestrel intrauterine contraceptive device (LNG-IUCD) on menstrual blood loss and its acceptance in Indian women with Heavy menstrual bleeding (HMB). Methods: 50 women with HMB and meeting the inclusion criteria were enrolled in the prospective non-randomized observational study from November 2013-2014 in PGIMER, RML HOSPITAL, a tertiary care hospital. LNG-IUCD was inserted and patients were followed up for six months. Reduction in menstrual blood loss, reduction in endometrial thickness, improvement in hemoglobin and serum ferritin and side effects due to LNG-IUCD was noted. Results: LNG-IUCD was effective in 47 out of 50 patients suffering from HMB. There was 98% reduction in menstrual blood loss (PBAC score) and 67.8% reduction in endometrial thickness after six months. Improvement in hemoglobin was by 2.44 gm/dl whereas serum ferritin improved by 15.39 µg/l after 6 months. Relief in dysmenorrhea was 94.7%. Complete amenorrhea was achieved in 19.14% and 44.6% were suffering from spotting. Treatment failure was seen in 3 patients who expelled LNG-IUCD at varying intervals. One patient with misplaced LNG-IUCD was relieved of symptoms after repositioning. Proper counseling prior to insertion and after insertion made LNG-IUCD well accepted in our study population. Conclusions: LNG-IUCD is an effective and acceptable non-surgical alternative to a common problem of HMB. The success rate was 94% in our study with only 3 patients needing hysterectomy due to expulsion. Emphasis on counseling patients of troublesome spotting and correct fundal placement is essential.